PEACE (HOMOLOGATION) IN BANKRUPTCY AFTER THE DEBTOR IS DECLARED IN BANKRUPT BECAUSE PEACE (HOMOLOGATION) IN PKPU IS NOT ACCEPTED - HORMAN SIREGAR (Awang Long Law Review, 2021)
settle the payment of the debt given by the creditor. Bankruptcy can occur due to 2 (two) things, first because it is filed for bankruptcy, and second because it is requested by PKPU but in PKPU it is not successful in achieving a peace (homologation). In the PKPU Process, the Debtor is given the opportunity to submit a reconciliation plan which contains the condition of the Debtor and the scheme/procedure for payment of debt to be carried out by the Debtor against his Creditors. If the conciliation plan is accepted by the creditor, the debtor's PKPU will end and he can resume his business independently as before. However, if the reconciliation plan proposed by the Debtor is not accepted by the Creditor, the Debtor will fall into bankruptcy. In the event that the Debtor is declared bankrupt, the Curator appointed by the Court will exercise his authority to administer and settle the bankruptcy estate. The problem is, Can the Bankrupt Debtor be able to resubmit the reconciliation plan during the Bankruptcy process and How is the implementation of its authority for the Curator to manage and settle the assets of the Bankruptcy Debtor who proposes reconciliation in Bankruptcy? The purpose of this study is to analyze and find out the Bankrupt Debtor in resubmitting the Peace Proposal in the Bankruptcy Process after the Peace in the PKPU Process failed/not achieved, and to determine the authority of the Curator in managing and settling bankruptcy assets against the Debtor who is submitting a peace plan in the Bankruptcy process. Research Methods using normative juridical research methods. namely library research and analysis of cases. Based on the results of the study, it was concluded that Bankrupt Debtors who had been declared Bankrupt with all the legal consequences could still submit proposals for reconciliation to their Creditors, even though the Peace in PKPU had been submitted but was not achieved. The legal position of the debtor whose bankruptcy has ended due to reconciliation (homologation) returns to its original state of managing and running its business independently.